BILINGUALISM OF LANGUAGE LEARNING IN ISLAMIC SCHOOL (ETHNOGRAPHIC RESEARCH IN DAARUL RAHMAN ISLAMIC SCHOOL I, SOUTH JAKARTA) - Fitriyani, Fitriyani; Rasyid, Yumna (IJLECR (International Journal of Language Education and Cultural Review), 2018)
The aims of this research are to examine deeply the process of bilingualism language learning, the environment of language learning bilingualism, the teacher’s involvement of teachers of bilingualism language learning, the students’ participation in the bilingualism language learning and the evaluation of bilingualism language learning in Daarul Rahman I Islamic Schools, South Jakarta. This a qualitative research with the ethnographic approach. The informants in this study are age-level of High School students. The method of data collection is done by observation, interview and documentation. The results of this study shows that the learning process of Arabic language and English in the neighborhood of Daarul Rahman I Islamic School is a tradition experiences the development of suitable students and science in the millennial. In addition, the environment of language learning is very conducive. The involvement of teachers in language learning rise learning culture which is integrated and student-centered. While, the involvement of students in language learning belongs to communicative learning and culture rise to active and disciplined in speaking. Evaluation in language learning includes written and unwritten test, focuses upon four languages proficiency.